Meet the Expert : Barr Moses on Eliminating Data Downtime - Moses, Barr (O'Reilly Media, Inc., 2021)
Ever had your CEO look at a report and say the numbers look way off? Has a customer ever called out incorrect data in one of your product dashboards? If this sounds familiar, data reliability should be the cornerstone of your data strategy. In this talk, Barr Moses will introduce the concept of "data downtime"--Periods of time when data is partial, erroneous, missing or otherwise inaccurate. Data downtime is highly costly for organizations, yet is often addressed ad hoc. The solution? Data observability, an approach to tackling data downtime that leverages core principles of software engineering. We'll discuss why data downtime matters to the data industry and share data observability tactics best-in-class organizations use to address it. Join us for this edition of Meet the Expert with Barr Moses to learn how to address data downtime and make observability a pillar of your data strategy. O'Reilly Meet the Expert explores emerging business and technology topics and ideas through a series of one-hour interactive events. You'll engage in a live conversation with experts, sharing your questions and ideas while hearing their unique perspectives, insights, fears, and predictions